If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5u + 5(1 + -6) = u + 8 Combine like terms: 1 + -6 = -5 5u + 5(-5) = u + 8 Multiply 5 * -5 5u + -25 = u + 8 Reorder the terms: -25 + 5u = u + 8 Reorder the terms: -25 + 5u = 8 + u Solving -25 + 5u = 8 + u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-1u' to each side of the equation. -25 + 5u + -1u = 8 + u + -1u Combine like terms: 5u + -1u = 4u -25 + 4u = 8 + u + -1u Combine like terms: u + -1u = 0 -25 + 4u = 8 + 0 -25 + 4u = 8 Add '25' to each side of the equation. -25 + 25 + 4u = 8 + 25 Combine like terms: -25 + 25 = 0 0 + 4u = 8 + 25 4u = 8 + 25 Combine like terms: 8 + 25 = 33 4u = 33 Divide each side by '4'. u = 8.25 Simplifying u = 8.25
| 5x-3=6x+2x-9 | | 2cos^2(x)-sin(x)=0 | | 4*ln(x)-x=6 | | -3+6=2x-9 | | X^5/3=0.5 | | 10x-7(3)=-18 | | 17a-4= | | 4(3x-8)=28 | | 16y-10=14 | | 1/3(6x=2x | | 8x+8=3x+73 | | 3ln(2x+1)-5=1 | | (3x-x)+(8x+9)= | | x^3-2x^2+36=0 | | 4(5x-8)-13x=24 | | (12y*12y-144)=(3y*3y) | | x^2+(6x+17)=0 | | n+6-2=1 | | 2+c-3=3 | | X^4-3x^2+4x-6=0 | | F(x)=-3x+5 | | (cd+2)+cd-4= | | x^2-(m+1)x-5=0 | | (8x+4)=(5x+2) | | Sinx=0.75 | | 2a+16+b=18+b | | 9x+26x^2=3 | | 6y-2=2y+7 | | 8+3x+x=20 | | 58474+46274= | | t=5(2)+3(4) | | 15-3x+2-8x=39 |